“Postcolonial Melancholia” In Abdulrazak Gurnah’s Pilgrims Way - Deepika. A; Ashok Kumar. K (Revista Electronica de Veterinaria, 2024)
This paper examines the representation of Postcolonial Melancholia in Abdulrazak Gurnah’s Pilgrims Way. It is the story of an orderly and disillusioned Zanzibari immigrant leading a marginal and melancholic life in the Britian. The paper focuses on Gilroy’s concept of Postcolonial Melancholia, which can serve as a theoretical framework to analyze the protagonist Daud's experiences. The paper discusses how the protagonist Daud negotiates his orderly position in conditions of race and migration. The paper also focuses on the colonial past and the progressive reconstruction of his identity through his attachment to Catherine Mason. Additionally, it addresses the psychological distress and sense of dislocation produced by his displacement to racially prejudiced Britain. By situating Daud’s personal struggles within broader socio-historical contexts, this paper underscores the enduring impact of colonial histories on contemporary postcolonial identities and experiences.